Anti-GD2 immunotherapy for neuroblastoma. Issue 10 (3rd October 2017) - Sait, Sameer; Modak, Shakeel
ABSTRACT: Introduction : Current therapeutic approaches for high-risk neuroblastoma (HR-NB) include high-dose chemotherapy, surgery and radiotherapy; interventions that are associated with long and short-term toxicities. Effective immunotherapy holds particular promise for improving survival and quality of life by reducing exposure to cytotoxic agents. GD2, a surface glycolipid is the most common target for immunotherapy. Areas covered : We review the status of anti-GD2 immunotherapies currently in clinical use for neuroblastomas and novel GD2-targeted strategies in preclinical development. Expert commentary : Anti-GD2 monoclonal antibodies are associated with improved survival in patients in their first remission and are increasingly being used for chemorefractory and relapsed neuroblastoma. As protein engineering technology has become more accessible, newer antibody constructs are being tested. GD2 is also being targeted by natural killer cells and T-cells. Active immunity can be elicited by anti-GD2 vaccines. The rational combination of currently available and soon-to-emerge immunotherapeutic approaches, and their integration into conventional multimodality therapies will require further investigation to optimize their use for HR-NB.